2020
DOI: 10.1136/medhum-2020-011940
|View full text |Cite
|
Sign up to set email alerts
|

Person-ness of voices in lived experience accounts of psychosis: combining literary linguistics and clinical psychology

Abstract: In this paper, we use concepts and insights from the literary linguistic study of story-world characters to shed new light on the nature of voices as social agents in the context of lived experience accounts of voice-hearing. We demonstrate a considerable overlap between approaches to voices as social agents in clinical psychology and the perception of characters in the linguistic study of fiction, but argue that the literary linguistic approach facilitates a much more nuanced account of the different degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this instance, we have provided data triangulation through using a range of methods (from psychology and from corpus linguistics) on the same dataset, as well as investigator triangulation in the researchers who carried out the separate analyses. Furthermore, our operationalisation of concepts as they are defined in clinical psychology (voice, personification, complexity) has also drawn on related concepts from linguistics, such as the grammatical realisation of agency and a view of personification informed by literary linguistics (Semino et al, 2021). This demonstrates one way in which qualitative coding approaches can be substantiated by quantitative and qualitative linguistic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, we have provided data triangulation through using a range of methods (from psychology and from corpus linguistics) on the same dataset, as well as investigator triangulation in the researchers who carried out the separate analyses. Furthermore, our operationalisation of concepts as they are defined in clinical psychology (voice, personification, complexity) has also drawn on related concepts from linguistics, such as the grammatical realisation of agency and a view of personification informed by literary linguistics (Semino et al, 2021). This demonstrates one way in which qualitative coding approaches can be substantiated by quantitative and qualitative linguistic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One exception is Semino et al (2021), who use concepts and insights from the literary linguistic study of story-world characters to shed new light on the nature and degree of voices as social agents. In this paper, we go beyond the qualitative approach adopted by Semino et al (2021) by exploiting the potential of corpus linguistic methods to triangulate the findings of psychological research relying on different methods and ultimately to contribute to creating "scalable, inexpensive screening measures or risk assessments that may be administered by a wider variety of healthcare professionals in a broad range of contexts" (Resnik et al, 2014: iii). One existing tool that offers quantitative linguistic analysis of psychological phenomena such as trauma, bereavement, deception etc.…”
Section: Minimal Personificationmentioning
confidence: 99%
“…For the majority of the participants, particularly those on the wards, illusory social agents appeared frequently and were relatively dynamic characters that sometimes irritated or angered the participants but at other times offered comfort and humour. Based on the scalar model of minimal to complex personification of voices developed by Semino et al (2020), these qualities of (i) having 'online' emotions, (ii) possessing internal states and motivations that are not accessible to the participants, (iii) engaging in interactions with participants, and (iv) having different behaviours, suggest that many social agents are personified in complex ways that are similar to the way real people are perceived in the shared external social world. Notably, Wilkinson and Bell (2016) suggested that 'externally individuated' illusory social agents in psychosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the scalar model of minimal to complex personification of voices developed by Semino, Demjén, and Collins ( 2020 ), these qualities of (i) having ‘online’ emotions, (ii) possessing internal states and motivations that are not accessible to the participants, (iii) engaging in interactions with participants, and (iv) having different behaviours suggest that many social agents are personified in complex ways that are similar to the way real people are perceived in the shared external social world. Notably, Wilkinson and Bell ( 2016 ) suggested that ‘externally individuated’ illusory social agents in psychosis (i.e., those that do correspond to external identities) reflect a richer agent representation than internally individuated ones, but the evidence presented here suggests that internally individuated agents may be equally as rich in terms of their human‐like agentive properties.…”
Section: Discussionmentioning
confidence: 99%